Analisis Perkembangan Kognitif Pada Anak Usia Dini Di Desa Ngabar Siman Ponorogo - Yuli Umro'atin Yuli (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
The development of cognition means the development of children in using their thinking powers. In cognitive development, children, in this case their brain, begin to develop the ability to think, learn and remember. The cognitive world of children at this age is creative, free, and fantastic. Children's imaginations develop over time, and their mental understanding of the world improves. At this level, children can improve their use of language by imitating adult behavior. One thing in learning is that it should be better to look to the future, to learn to anticipate the realities of life. This is very important for children who live in an era of globalization that demands openness and flexibility in thinking, as well as the ability to solve non-routine problems creatively and critically. Early childhood cognitive development in Ngabar village is very diverse. Some are developing very fast, some are moderate and some are slow. This cognitive development is largely due to the learning process in preschool and not a little because of family and inherent factors. With Kindergarten preschool education, children's cognitive development can be more focused because of the continuous guidance from their teachers. For early childhood who have not been mentored by an educator or teacher, they learn to know something in their family and environment.